Political Representation in Indian Democracy: A View from the Margins. Issue 1 (June 2019) - Mehrotra, Ishita
Abstract: Political participation and representation are pillars of a successful democracy. This article explores Indian democracy from the perspective of village-based Dalit women; it is about how Dalit women understand and engage with the 'political' and how they see their representatives. The argument built in the article is that Dalit women see politics and representation from the vantage point of their everyday experiences and from their distinct positions in terms of caste, class and gender.